TI_GERICHTE 52.2019.498 vom 4. September 2019 , Licenza edilizia per uno stabile residenziale-commerciale e centro medico - TI Tribunale d'appello (2019)
Licenza edilizia per uno stabile residenziale-commerciale e centro medico